Acoustic Variation of Syllable-Initial [ŋ] in Zhengding Chinese - Ma, Yanxiao (International Journal of Linguistics, 2021)
The study explores the acoustic properties of syllable-initial [ŋ] in Zhengding dialect, to see whether the younger generation shows the same pattern with the senior group. 60 items with vowel realizations [ʌ, a, ɑ, ə, ɤ] and [ai, ɑo, ou] in ‘[ŋ]-V’ and ‘[g]-V’ structures are produced by 8 native speakers. Three experiments are conducted. Experiment I compares ‘[ŋ]-V’ and ‘[g]-V’ structures in senior speeches. Three acoustic effects due to the initial [ŋ] are established: vowels become less distinctive from each other by decreasing the first formant (F1), increasing the second formant (F2), and shrinking the gap between the second formant (F2) and the third formant (F3). Experiment II is conducted between ‘[ŋ]-V’ and ‘[g]-V’ in the younger speakers, investigating whether they have a similar pattern with the seniors. Experiment III is supplemented to compare the younger speeches in Zhengding dialect and Mandarin, to explore whether the generational variation in Zhengding dialect is relevant to dialect contact, i.e., whether the younger speakers are largely influenced by Mandarin. The result shows the younger generation does not produce the initial [ŋ] with the vowel realizations [ʌ, a, ɑ, ə, ai, ɑo, ou], which traditionally have an initial [ŋ], with an exception in [ɤ]. A fusion process is assumed in [ɤ] in the younger pattern, in which the initial nasal [ŋ] and the following vowel [ɤ] are combined into the single nasalized vowel [ɤ̃], with the nasal effects remained, but the initial nasal then deleted. From the sociovariationist perspective, the nasal-initial pronunciation is a partial variation in Zhengding dialect. Not all speakers pronounce with the velar-initial [ŋ]. The older generation largely remained the velar-initial variant, but the younger generation preferred the zero-onset, which might be due to the influence of dialect contact with Mandarin.